Pengembangan Lembar Kegiatan Mahasiswa (LKM) Fisika Dasar Berbasis Pendekatan Scaffolding Terintegrasi Alquran untuk Mahasiswa MIPA - Artha Nesa Chandra; Novia Lizelwati (Natural Science, 2023)
This research is motivated by the fact in the field that many students experience difficulties in basic physics lectures caused by learning methods, task difficulties, and inappropriate learning methods. Lecturers have difficulty providing an understanding of physics to students, because many students have misconceptions about physics from high school. Students are used to the physics learning style they brought from high school, such as relaxed learning, the teacher gives formulas instead of understanding physics concepts. As well as referring to one of the missions of the FTIK IAIN Batusangkar that lecturer activities must integrate the Al-Qur’an and hadith. The purpose of this research is to produce a basic physics Student Activity Sheet integrating the Al-Qur’an with scaffolding approach a valid and practical. This research is a type of development research with the ADDIE model. The research instruments used were validation sheets and student response questionnaire sheets. Based on the results of product are in the very valid category with a percentage of 84, 00%. Results from student and lecturer response questionnaires found that the student developed were practical with a percentage of 84, 81% and 75, 00% in the very practical category and practical category